Cover Image. (30th December 2021) - Bordier, Cecile; Weil, Georg; Bach, Patrick; Scuppa, Giulia; Nicolini, Carlo; Forcellini, Giulia; Pérez‐Ramirez, Ursula; Moratal, David; Canals, Santiago; Hoffmann, Sabine; Hermann, Derik; Vollstädt‐Klein, Sabine; et al.
Abstract : The cover image is based on the Original Article Increased network centrality of the anterior insula in early abstinence from alcohol by Cecile Bordier et al., https://doi.org/10.1111/adb.13096 .